2020
DOI: 10.1007/s00228-020-03050-4
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and management outcomes of pharmacogenetic CYP2C19 testing for clopidogrel therapy in clinical practice

Abstract: Purpose The antiplatelet prodrug clopidogrel is bioactivated by the polymorphic enzyme CYP2C19. Prospective clinical studies demonstrated an association between CYP2C19 loss of function (LoF) variants and an increased risk of thrombotic events under clopidogrel, but pharmacogenetic (PGx) testing is not frequently implemented in clinical practice. We report our experience with PGx-guided clopidogrel therapy with particular regard to clinically relevant patient management changes. Methods We conducted an observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
(85 reference statements)
4
5
0
Order By: Relevance
“…Our results are consistent with previous studies of clopidogrel efficacy in CYP2C19 LoF genotype carriers, although the previous evidence was predominantly from high-risk acutely hospitalized patient groups (24)(25)(26)(27), with limited follow-up periods (rarely over 12 months). Some studies reported that the effect of CYP2C19 genotype on reducing clopidogrel efficacy was limited to the short-term (1-6 months) only (28,29), but in our community based longer term follow-up we found no evidence for deviation from the proportional hazards assumptions, with survival analysis results suggesting sustained effects over the follow-up period.…”
Section: Cyp2c19 Lof Genetic Variants (Implying Intermediate or Low Metabolizer Status) Have Beensupporting
confidence: 92%
“…Our results are consistent with previous studies of clopidogrel efficacy in CYP2C19 LoF genotype carriers, although the previous evidence was predominantly from high-risk acutely hospitalized patient groups (24)(25)(26)(27), with limited follow-up periods (rarely over 12 months). Some studies reported that the effect of CYP2C19 genotype on reducing clopidogrel efficacy was limited to the short-term (1-6 months) only (28,29), but in our community based longer term follow-up we found no evidence for deviation from the proportional hazards assumptions, with survival analysis results suggesting sustained effects over the follow-up period.…”
Section: Cyp2c19 Lof Genetic Variants (Implying Intermediate or Low Metabolizer Status) Have Beensupporting
confidence: 92%
“…These must be addressed in prospective large controlled studies for specific PGx-guided therapy [4,20]. Nevertheless, we were able to perform a separate analysis for our PGx consultations in patients with clopidogrel therapy, and our results appear to be in line with those studies [18]. Another limitation concerns the 16-gene panel itself that we were able to use.…”
Section: Discussionmentioning
confidence: 82%
“…For example, PGx testing for clopidogrel and tamoxifen is merely classified as "actionable" according to PHARMGKB. But the lack of efficacy associated with the tested PGx variants is potentially lethal, and based on a review of the latest evidence, PGx expert guidelines, as well as our own clinical experience, we conclude that PGx testing indeed makes an important contribution to clinical decisions related to those frequently prescribed drugs and can even improve patient compliance [4][5][6][18][19][20]. Furthermore, one must realize that most PGx variants do not have a high predictive value for efficacy or adverse reactions of a drug in individual patients.…”
Section: Discussionmentioning
confidence: 83%
“…For example, PGx testing for clopidogrel and tamoxifen is merely classified as “actionable” according to PharmGKB. But the lack of efficacy associated with the tested PGx variants is potentially lethal, and, based on a review of the latest evidence, PGx expert guidelines, and our own clinical experience, we conclude that PGx testing indeed makes an important contribution to clinical decisions related to those frequently prescribed drugs and can even improve patient compliance [ 5 , 6 , 7 , 25 , 30 , 31 ]. On the other hand, one must realize that for many other drugs in spite of established statistically significant associations most PGx variants do not have a high predictive value for efficacy or adverse reactions of a drug in individual patients.…”
Section: Discussionmentioning
confidence: 98%
“…The 16-gene PGx panel test was able to detect variants that are clinically relevant according to the PharmGKB classification in 100% of tested patients. More important, results of PGx testing led to an actual change of medication or specific recommendations to do so in a high proportion of the tested patients [ 25 ]. These adjustments of current medication and specific recommendations regarding potential future medication were supported by a PGx expert system and implemented through personalized clinical pharmacology consultations.…”
Section: Discussionmentioning
confidence: 99%